DIÁLOGOS SOBRE A DOCÊNCIA: CONECTANDO EXPERIÊNCIAS - Aparecida Ferreira da Silva, Iranilda; Camilly Santos Silva, Kauane; Ferreira de Souza, Luciana; Pereira de Araújo Silva, Maria Iolanda; Carvaho Alvim, Marília; Pinheiro da Silva, Rebeca; Abadia de Sousa, Milena (Intercursos, 2025)
não consta